Association between socioeconomic and motherhood characteristics with receiving community-based treatment services among justice-involved young female drug users: a retrospective cohort study in Taiwan - Chuan-Yu Chen; Tan-Wen Hsieh; Wenmay Rei; Cheng-Hsiung Huang; Sheng-Chang Wang (BMC, 2024)
Abstract Background Drug-involved individuals who contact treatment services in Taiwan are mostly driven by criminal justice systems either as an alternative or adjunct to criminal sanctions for a drug offence. With a focus on justice-involved young female drug users, the present study examines the extent to which socioeconomic and motherhood characteristics are associated with receiving deferred prosecution, a scheme diverting drug offenders to community-based addiction treatment. Methods We identified a cohort of 5869 women under the age of 30 arrested for using Schedule II drugs (primarily amphetamine-like stimulants) from the 2011-2017 National Police Criminal Records in Taiwan. Information concerning socioeconomic characteristics, pregnancy and live birth history, and deferred prosecution was obtained through linkage with the 2006-2019 National Health Insurance, birth registration, and deferred prosecution datasets. Multinomial logistic regression was used to evaluate the association with stratification by recidivism status. Results Within six months of arrest, 21% of first-time offenders (n = 2645) received deferred prosecution and 23% received correction-based rehabilitation; the corresponding estimates for recidivists (n = 3224) were 6% and 15%, respectively. Among first-time offenders, low/unstable income was associated with lower odds of deferred prosecution (adjusted odds ratio [aOR] = 0.71; 95% CI: 0.58, 0.88). For recidivists, those with low/unstable income (aOR = 1.58) or unemployment (aOR = 1.58) had higher odds of correction-based rehabilitation; being pregnant at arrest was linked with reduced odds of deferred prosecution (aOR = 0.31, 95% CI: 0.13, 0.71) and correction-based rehabilitation (aOR = 0.50, 95% CI: 0.32, 0.77). Conclusions For the young women arrested for drug offences, disadvantaged socioeconomic conditions were generally unfavored by the diversion to treatment in the community. Childbearing upon arrest may lower not only the odds of receiving medical treatment but also correctional intervention. The criminal prosecution policy and process should be informed by female drug offenders' need for treatment and recovery.